Perspectives of targeting LILRB1 in innate and adaptive immune checkpoint therapy of cancer - Zeller, Tobias; Münnich, Ira A.; Windisch, Roland; Hilger, Patricia; Schewe, Denis M.; Humpe, Andreas; Kellner, Christian (Frontiers in Immunology, 2023)
Immune checkpoint blockade is a compelling approach in tumor immunotherapy. Blocking inhibitory pathways in T cells has demonstrated clinical efficacy in different types of cancer and may hold potential to also stimulate innate immune responses. A novel emerging potential target for immune checkpoint therapy is leukocyte immunoglobulin-like receptor subfamily B member 1 (LILRB1). LILRB1 belongs to the superfamily of leukocyte immunoglobulin-like receptors and exerts inhibitory functions. The receptor is expressed by a variety of immune cells including macrophages as well as certain cytotoxic lymphocytes and contributes to the regulation of different immune responses by interaction with classical as well as non-classical human leukocyte antigen (HLA) class I molecules. LILRB1 has gained increasing attention as it has been demonstrated to function as a phagocytosis checkpoint on macrophages by recognizing HLA class I, which represents a ‘Don’t Eat Me!’ signal that impairs phagocytic uptake of cancer cells, similar to CD47. The specific blockade of the HLA class I:LILRB1 axis may provide an option to promote phagocytosis by macrophages and also to enhance cytotoxic functions of T cells and natural killer (NK) cells. Currently, LILRB1 specific antibodies are in different stages of pre-clinical and clinical development. In this review, we introduce LILRB1 and highlight the features that make this immune checkpoint a promising target for cancer immunotherapy.